Panhypopituitarism after tuberculous meningitis with suprasellar abscess. (4th April 2011) - Iyer, D; Lissauer, S; Jones, G; Karandikar, S; Shaw, N; Walsh, R; Denniston, S; Hackett, S; Welch, S
Abstract : Background: Central nervous system tuberculosis in children accounts for 2.2% of tuberculosis in England and Wales at presentation. Suprasellar tubercular abscess is extremely rare, especially in children, with only a few cases reported worldwide. Case report: A 15 year old, previously well, Somalian boy presented with 4 week history of intermittent nocturnal fever and sore throat. He had moved from Somalia to the UK 4 months prior to presentation. His clinical examination, chest x-ray and initial blood tests were unremarkable. The following day, he was noted to be confused and had multiple, brief generalised tonic clonic seizures. He was intubated for airway protection and urgent CT scan of head showed multiple, multilocular ring enhancing lesions extending from suprasellar cistern into the hypothalamus. Cerebrospinal fluid examination revealed 102 white cells (97 lymphocytes), 2.79 g/l protein, but no organisms on gram and acid fast staining. Clinical diagnosis of tuberculous abscess was made. Quadruple anti-tuberculous medications and prednisolone were commenced. Subsequently, his mantoux test was strongly positive. Smears from gastric washings and endotracheal aspirates were negative for acid fast bacilli and culture results are awaited. He was monitored on intensive care where he was noted to have polyuria. For further management he was transferred to regional neurosurgical unit where he was managed conservatively, although, persisted to have polyuria and polydipsia. Investigations revealed hypernatraemia (151 mmol/l) with low urine osmolality (307 mOsm/l) suggesting diabetes insipidus. Further endocrine investigations confirmed panhypopituitarism. He was started on oral thyroxine, DDAVP, hydrocortisone and monthly intramuscular injections of testosterone. He is making good clinical progress. His MRI scan 6 weeks after initial diagnosis revealed no change in the tuberculoma with no new tuberculomas or hydrocephalus. Conclusion: Suprasellar tubercular abscess is extremely rare form of tuberculosis in children. It can be associated with significant endocrine abnormalities, which require high index of clinical suspicion and prompt investigations.